2017
DOI: 10.2106/jbjs.16.00878
|View full text |Cite
|
Sign up to set email alerts
|

Highly Cross-Linked Polyethylene Reduces Wear and Revision Rates in Total Hip Arthroplasty

Abstract: Therapeutic Level I. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(60 citation statements)
references
References 26 publications
2
52
1
4
Order By: Relevance
“…2). Volumetric wear is a 3-dimensional measurement of femoral head penetration using additional formulations that assume cylindrical loss along its linear path [3,17]. Manual analysis and ellipse correction were specifically selected as software settings for analysis.…”
Section: Wear Ratesmentioning
confidence: 99%
“…2). Volumetric wear is a 3-dimensional measurement of femoral head penetration using additional formulations that assume cylindrical loss along its linear path [3,17]. Manual analysis and ellipse correction were specifically selected as software settings for analysis.…”
Section: Wear Ratesmentioning
confidence: 99%
“…Osteolysis related to polyethylene debris is a well-documented cause of late revision total hip arthroplasty (THA) [1]. However, modern highly cross-linked polyethylene has shown favorable wear properties in THA and is associated with longer survival compared to conventional polyethylene [2].…”
Section: Introductionmentioning
confidence: 99%
“…The wear rates of metal‐on‐cross‐linked‐polyethylene (MoXLPE) bearing couples are typically less than 11 mm 3 /million cycles (Mc) compared with metal‐on‐non‐XLPE, which have reported wear rates ranging from 10 to 51 mm 3 /Mc . Clinical trials and mid‐ to long‐term follow‐up studies of XLPE have shown significantly reduced wear, less osteolysis, and a lower risk of revision than conventional non‐XLPE . A further point to note is that the revision rates for MoXLPE appear to vary according to the size of the femoral head, with 32‐mm femoral heads showing the lowest wear for MoXLPE in the AOANJRR…”
Section: Introductionmentioning
confidence: 99%
“…14,19,20 Clinical trials and mid-to long-term follow-up studies of XLPE have shown significantly reduced wear, less osteolysis, and a lower risk of revision than conventional non-XLPE. [21][22][23][24] A further point to note is that the revision rates for MoXLPE appear to vary according to the size of the femoral head, 4,5 with 32-mm femoral heads showing the lowest wear for MoXLPE in the AOANJRR. 5 A recent retrospective observational study by Matharu et al compared adverse reaction to metal debris (ARMD) revision risk in different commonly implanted metal-on-metal (MoM) and non-MoM (MoP, ceramic-on-ceramic, and ceramic-on-polyethylene) bearing couples using data from the NJR.…”
Section: Introductionmentioning
confidence: 99%